Infectious diseases affecting the small bowel – what not to miss. Issue 3 (May 2021) - Keuchel, Martin; Bota, Marc; Baltes, Peter
Abstract : Purpose of review: This review summarizes infectious diseases involving the small bowel (SB) with a focus on recent literature related to diagnosis and pathophysiology. Recent findings: Typical symptom for SB infections is diarrhea, mostly self-limiting. Pathogens include bacteria, viruses, fungi, protozoan parasites, and helminths. Host–pathogen interaction is of special interest in infections with potentially severe or prolonged course. Research uses increasingly enterocyte cell culture systems. SARS-CoV2 can also infect enterocytes via angiotensin converting enzyme 2 (ACE2) receptor and causes gastrointestinal complaints in some patients. Chronic SB infections as tuberculosis, Cytomegalovirus, or Epstein–Barr virus have to be differentiated from Crohn's and other diseases. Severe rare fungal and protozoan parasitic infections can cause relevant morbidity in immunocompromised patients. Soil-transmitted helminthic infections are a special issue in endemic areas. Summary: Many infections involve the SB, typically causing mild and self-limiting diarrhea. Symptomatic therapy, hygiene, and isolation are the mainstay of management. However, some patients develop severe or chronic disease. Immunosuppression is a major cause for severe, but also for rare opportunistic systemic infections that can also affect the SB.